EPHA7 haploinsufficiency is associated with a neurodevelopmental disorder. Issue 4 (1st July 2021) - Lévy, Jonathan; Schell, Bérénice; Nasser, Hala; Rachid, Myriam; Ruaud, Lyse; Couque, Nathalie; Callier, Patrick; Faivre, Laurence; Marle, Nathalie; Engwerda, Aafke; van Ravenswaaij‐Arts, Conny M. A.; Plutino, Morgane; et al.
Abstract: Ephrin receptor and their ligands, the ephrins, are widely expressed in the developing brain. They are implicated in several developmental processes that are crucial for brain development. Deletions in genes encoding for members of the Eph/ephrin receptor family were reported in several neurodevelopmental disorders. The ephrin receptor A7 gene ( EPHA7 ) encodes a member of ephrin receptor subfamily of the protein‐tyrosine kinase family. EPHA7 plays a role in corticogenesis processes, determines brain size and shape, and is involved in development of the central nervous system. One patient only was reported so far with a de novo deletion encompassing EPHA7 in 6q16.1. We report 12 additional patients from nine unrelated pedigrees with similar deletions. The deletions were inherited in nine out of 12 patients, suggesting variable expressivity and incomplete penetrance. Four patients had tiny deletions involving only EPHA7, suggesting a critical role of EPHA7 in a neurodevelopmental disability phenotype. We provide further evidence for EPHA7 deletion as a risk factor for neurodevelopmental disorder and delineate its clinical phenotype. Abstract : Mapping of the 6q16.1 deletions encompassing EPHA7 (highlighted in blue) in our patients (red bar). Four out of 12 patients have deletions encompassing only EPHA7 and share a similar phenotype, suggesting the role of EPHA7 deletion as a risk factor for neurodevelopmental disorder with developmental delay/intellectual disability, speech delay, behavioral anomalies, and/or microcephaly. The deletions were inherited in nine out of 12 patients, suggesting variable expressivity and incomplete penetrance.